2015
DOI: 10.3168/jds.2015-9378
|View full text |Cite
|
Sign up to set email alerts
|

The Cornell Net Carbohydrate and Protein System: Updates to the model and evaluation of version 6.5

Abstract: New laboratory and animal sampling methods and data have been generated over the last 10 yr that had the potential to improve the predictions for energy, protein, and AA supply and requirements in the Cornell Net Carbohydrate and Protein System (CNCPS). The objectives of this study were to describe updates to the CNCPS and evaluate model performance against both literature and on-farm data. The changes to the feed library were significant and are reported in a separate manuscript. Degradation rates of protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
187
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(199 citation statements)
references
References 69 publications
7
187
1
4
Order By: Relevance
“…Likewise, Velle et al (1997) infused free AA into the rumen at various rates and showed that up to 20% could escape degradation and flow through to the small intestine, which is in agreement with data from Volden et al (1998). Van Amburgh et al (2010) suggested it might be more appropriate to redefine the protein A1 fraction from NPN as described by Krishnamoorthy et al (1982) to ammonia. This would shift small peptides and free AA currently associated with the A1 fraction into the A2 fraction, where they could contribute to MP supply, and also refines the prediction of rumen N balance as less N is degraded in the rumen.…”
Section: Analytical Techniques and Fractionationsupporting
confidence: 73%
See 1 more Smart Citation
“…Likewise, Velle et al (1997) infused free AA into the rumen at various rates and showed that up to 20% could escape degradation and flow through to the small intestine, which is in agreement with data from Volden et al (1998). Van Amburgh et al (2010) suggested it might be more appropriate to redefine the protein A1 fraction from NPN as described by Krishnamoorthy et al (1982) to ammonia. This would shift small peptides and free AA currently associated with the A1 fraction into the A2 fraction, where they could contribute to MP supply, and also refines the prediction of rumen N balance as less N is degraded in the rumen.…”
Section: Analytical Techniques and Fractionationsupporting
confidence: 73%
“…The intended methods for analyzing each major chemical component for use in the CNCPS are reported, as well as a sensitivity analysis of model outputs to variation in feed library inputs. An evaluation of model outputs and sensitivity relative to animal data is provided in a companion paper (Van Amburgh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This energy system is actually not ideal and therefore, current system has to be moved towards metabolizable energy (ME) or even net energy (NE) system (NRC, 2007;Van Duinkerken et al, 2011;Van Amburgh et al, 2015). Further, TDN data from various diets were obtained by estimations from their chemical composition and seldomly derived experimentally; such predictions may not be accurate since no study so far, to our knowledge, has validated the relationship between estimated TDN and measured TDN in the country.…”
Section: Energy Requirement Of Sheepmentioning
confidence: 99%
“…This system is less accurate and current system has to be shifted to metabolizable protein (MP) system or its equivalent (NRC, 2007;Van Duinkerken et al, 2011;Das et al, 2014;Owens et al, 2014;Van Amburgh et al, 2015). The old CP system has a main disadvantage, i.e.…”
Section: Protein Requirement Of Sheepmentioning
confidence: 99%
“…La dinámica y la sincronía de degradación de los nutrientes permiten una mayor eficiencia en la digestibilidad del alimento, resultando en una mayor disponibilidad de nutrientes para los microorganismos del rumen y el hospedero (Russell et al, 1992). Es por esto que, los modelos de simulación de las dinámicas ruminales consideran las diferentes tasas de degradación de los nutrientes, lo cual permite explicar de una manera más aproximada los procesos de fermentación ruminal (NRC, 2001; Van-Amburgh et al, 2015). En este sentido, la alimentación de rumiantes debe estar enfocada en la degradación sincrónica de los nutrientes, lo que permite una mayor síntesis de proteína microbial y un mayor rendimiento productivo del animal (Miller et al, 2001).…”
Section: Resultados Y Discusiónunclassified